Organic Selenium Increased Gilts Antioxidant Capacity, Immune Function, and Changed Intestinal Microbiota - Li, Zimei; Dong, Yanpeng; Chen, Sirun; Jia, Xinlin; Jiang, Xuemei; Che, Lianqiang; Lin, Yan; Li, Jian; Feng, Bin; Fang, Zhengfeng; Zhuo, Yong; Wang, Jianping; et al. (Frontiers in Microbiology, 2021)
Selenium is an indispensable essential micronutrient for humans and animals, and it can affect biological functions by combining into selenoproteins. The purpose of this study was to investigate the effects of 2-hydroxy-4-methylselenobutanoic acid (HMSeBA) on the antioxidant performance, immune function, and intestinal microbiota composition of gilts. From weaning to the nineteenth day after the second estrus, 36 gilts (Duroc×Landrace×Yorkshire) were assigned to three treatments: control group, sodium selenite group (0.3 mg Se/kg Na2SeO3) and HMSeBA group (0.3 mg Se/kg HMSeBA). Dietary supplementation with HMSeBA improved the gilts tissue selenium content (except in the thymus) and selenoprotein P concentration when compared to the Na2SeO3 or control group. Compared with the control group, the antioxidant enzyme activity in the tissues from gilts in the HMSeBA group were increased, and the concentration of malondialdehyde in the colon had a decreasing trend (P = 0.07). Gilts in the HMSeBA supplemented group had up-regulated gene expression of GPX2, GPX4 and SelX in spleen tissue, TrxR1 in thymus; GPX1 and SelX in duodenum, GPX3 and SEPHS2 in jejunum, and GPX1 in the ileum tissues (P < 0.05). In addition, compared with the control group, the expression of IL-1β, IL-6, IL-8 and MCP-1 in the liver, spleen, thymus, duodenum, ileum and jejunum of gilts in the HMSeBA group were down-regulated (P < 0.05), while the expression of IL-10 and TGF-β in the liver, thymus, jejunum and ileum were up-regulated (P < 0.05). Compared with the control group and the Na2SeO3 group, HMSeBA had increased concentration of serum cytokines IL-2 and IgG (P < 0.05), increased concentration of intestinal sIgA (P < 0.05), and decreased concentration of serum IL-6 (P < 0.05). Dietary supplementation with HMSeBA also increased the abundance of intestinal bacteria (Ruminococcaceae, Phascolarctobacterium; P < 0.05) and selectively inhibited the abundance of some bacteria (Parabacteroides, Prevotellaceae; P < 0.05). In short, HMSeBA improves the antioxidant performance and immune function of gilts, and changed the structure of the intestinal microflora. And this study provided data support for the application of HMSeBA in gilt and even pig production.